Metal–Organic Framework (MOF)-Derived Metal Oxides for Selective Catalytic Reduction (SCR) of NOx - Yu Zhang; Rui Wang (Molecules)
Metal–organic frameworks (MOFs) are a novel type of porous crystalline materials assembled from metal ions and organic linkers. Their derivatives can inherit characteristics such as high specific surface area, tunable porosity, and unique topological structures, which make MOF-derived metal oxides ideal catalysts for the selective catalytic reduction (SCR) of NOx. This review focuses on the synthetic strategies of MOF-derived metal oxides and the latest progress of oxides derived from various typical MOFs materials (including MILs, ZIFs, UiO, BTC series, MOF-74, MOF-5, and Prussian blue analogs, etc.) in the catalytic reduction in NOx, and analyzes the mechanisms for the enhanced catalytic performance. In addition, the challenges and prospects of MOF derivatives in catalytic applications are discussed. It is hoped that this review will help researchers understand the latest research progress of MOF-derived metal oxide materials in the catalytic removal of NOx pollution.